BACAAN DAN PEMBACAAN AL-QUR’AN YANG HIDUP DI MASYARAKAT - Rusydi, M (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
The Koran is a book of Muslims, which of the information itself mentions him with different names. Of these names at least we can identify the function and basic paradigm carries for Muslims in particular and humanity in general. Every Muslim believes that the Koran is the holy book of miracles and can solve human problems and save them not only in the world but also the hereafter. Thus the Koran always pay attention to the safety and welfare of mankind in the world and the hereafter. This is the paradigm which is owned by the Koran. Unfortunately, the recent reality does not show it. Koran only a Muslim home decor and read without meaning. Soon, the Koran has lost its significance. Therefore, this article seeks to reflect the issues through a methodological approach. Reflection should show how to build a live reading of the Koran. although the writing still needs further reflection, I just hope it can inspire us to fix it